COF-supported zirconium oxyhydroxide as a versatile heterogeneous catalyst for Knoevenagel condensation and nerve agent hydrolysis - Shekhar, Pragalbh; Devulapalli, Venkata Swaroopa Datta; Reji, Reshma; Singh, Himan Dev; Jose, Aleena; Singh, Piyush; Torris, Arun; Vinod, Chatakudath P.; Tokarz III, John A.; Mahle, John J.; Peterson, Gregory W.; Borguet, Eric; et al. (iScience, 2023)
A composite of catalytic Lewis acidic zirconium oxyhydroxides (8 wt %) and a covalent organic framework (COF) was synthesized. X-ray diffraction and infrared (IR) spectroscopy reveal that COF's structure is pre-served after loading with zirconium oxyhydroxides. Electron microscopy confirms a homogeneous distri-bution of nano-to sub-micron-sized zirconium clusters in the COF. 3D X-ray tomography captures the micron-sized channels connecting the well-dispersed zirconium clusters on the COF. The crystalline ZrOx(OH)(y)@COF's nanostructure was model-optimized via simulated annealing methods. Using 0.8 mol % of the catalyst yielded a turnover number of 100-120 and a turnover frequency of 160-360 h(-1) for Knoevenagel condensation in aqueous medium. Additionally, 2.2 mol % of catalyst catalyzes the hy-drolysis of dimethyl nitrophenyl phosphate, a simulant of nerve agent Soman, with a conversion rate of 37% in 180 min. The hydrolytic detoxification of the live agent Soman is also achieved. Our study unveils COF-stabilized ZrOx(OH)(y) as a new class of zirconium-based Lewis + Bronsted-acid catalysts.

Cathode|electrolyte interface engineering by a hydrogel polymer electrolyte for a 3D porous high-voltage cathode material in a quasi-solid-state zinc metal battery by in situ polymerization - Puthiyaveetil, Priyanka Pandinhare; Torris, Arun; Dilwale, Swati; Kanheerampockil, Fayis; Kurungot, Sreekumar (SMALL, 2024)
This work highlights the development of a superior cathode|electrolyte interface for the quasi solid-state rechargeable zinc metal battery (QSS-RZMB) by a novel hydrogel polymer electrolyte using an ultraviolet (UV) light-assisted in situ polymerization strategy. By integrating the cathode with a thin layer of the hydrogel polymer electrolyte, this technique produces an integrated interface that ensures quick Zn2+ ion conduction. The coexistence of nanowires for direct electron routes and the enhanced electrolyte ion infiltration and diffusion by the 3D porous flower structure with a wide open surface of the Zn-MnO electrode complements the interface formation during the in situ polymerization process. The QSS-RZMB configured with an integrated cathode (i-Zn-MnO) and the hydrogel polymer electrolyte (PHPZ-30) as the separator yields a comparable specific energy density of 214.14 Wh kg(-1) with that of its liquid counterpart (240.38 Wh kg(-1), 0.5 M Zn(CF3SO3)(2) aqueous electrolyte). Other noteworthy features of the presented QSS-RZMB system include its superior cycle life of over 1000 charge-discharge cycles and 85% capacity retention with 99% coulombic efficiency at the current density of 1.0 A g(-1), compared to only 60% capacity retention over 500 charge-discharge cycles displayed by the liquid-state system under the same operating conditions.
Keywords: cathode-electrolyte interface tuning; dendrite inhibition; epitaxial zinc deposition; hydrogel polymer electrolyte; In situ polymerization; Quasi solidstate rechargeable zinc metal battery